Sentiment classification using N-ary tree-structured gated recurrent unit networks - Tsakalos, Vasileios (2019)
Tsakalos, V., & Henriques, R. (2018). Sentiment classification using N-ary tree-structured gated recurrent unit networks. In A. Fred, & J. Filipe (Eds.), Proceedings of the 10th International Joint Conference on Knowledge Discovery, Knowledge Engineering and Knowledge Management (IC3K 2018) (Vol. 1, pp. 149-154). (IC3K 2018; Seville; Spain; 18-September) Scitepress. ISBN: 978-989-758-330-8